A versatile system to introduce clusters of genomic double‐strand breaks in large cell populations. Issue 5 (20th August 2020) - Kolb, Thorsten; Khalid, Umar; Simović, Milena; Ratnaparkhe, Manasi; Wong, John; Jauch, Anna; Schmezer, Peter; Rode, Agata; Sebban, Shulamit; Haag, Daniel; Hergt, Michaela; Devens, Frauke; et al.
Abstract: In vitro assays for clustered DNA lesions will facilitate the analysis of the mechanisms underlying complex genome rearrangements such as chromothripsis, including the recruitment of repair factors to sites of DNA double‐strand breaks (DSBs). We present a novel method generating localized DNA DSBs using UV irradiation with photomasks. The size of the damage foci and the spacing between lesions are fully adjustable, making the assay suitable for different cell types and targeted areas. We validated this setup with genomically stable epithelial cells, normal fibroblasts, pluripotent stem cells, and patient‐derived primary cultures. Our method does not require a specialized device such as a laser, making it accessible to a broad range of users. Sensitization by 5‐bromo‐2‐deoxyuridine incorporation is not required, which enables analyzing the DNA damage response in post‐mitotic cells. Irradiated cells can be cultivated further, followed by time‐lapse imaging or used for downstream biochemical analyses, thanks to the high throughput of the system. Importantly, we showed genome rearrangements in the irradiated cells, providing a proof of principle for the induction of structural variants by localized DNA lesions.